Process Optimization by DMAIC Approach in Algerian Industry (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The aim of this paper is to contribute to the improvement of the performance of the functioning of the SCIMAT company. For that purpose, we made a diagnosis of all workshops to identify the possible axes of improvement and to choose the solutions to be implemented.This diagnosis is made by implementation of DMAIC methodology of Six sigma approach at SCIMAT company in Algeria, DMAIC is the five-step approach that makes up the Six Sigma tool kit, and its sole objective is to drive costly variation from manufacturing and business processes. The five steps in DMAIC are Define, Measure, Analyze, Improve, and Control. As the backbone of the Six Sigma methodology, DMAIC delivers sustained defect-free performance and highly competitive quality costs over the long run.